Matching with Myopic and Farsighted Players - P. Jean-Jacques Herings; Ana Mauleon; Vincent Vannetelbosch (Fondazione Eni Enrico Mattei (FEEM), 2017)
We study stable sets for marriage problems under the assumption that players can be both myopic and farsighted. We introduce the new notion of the myopic-farsighted stable set. For the special cases where all players are myopic and where all players are farsighted, our concept predicts the set of matchings in the core. When all men are myopic and the top choice of each man is a farsighted woman, we show that the singleton consisting of the woman-optimal stable matching is a myopic-farsighted stable set. The same result holds when all women are farsighted.
Keywords: C70; C78; 330; Marriage Problems; Stable Sets; Myopic and Farsighted Players